Crown-Root Angulation of Central Incisors in Cases With Maxillary Lateral Incisors Agenesis - Ogodescu, Alexandru; Ştefănescu, Ramona; Ogodescu, Emilia; Igna, Andreea; Luca, Magda; Bolintineanu, Sorin (European Scientific Journal, ESJ, 2017)
Dental agenesis of the maxillary lateral incisor is a frequently seen anomaly in children and teenagers nowadays. It can alter the esthetics as well as the functions in the frontal area of the maxilla and therefore, early detection and therapy would be beneficial. The treatment often implies an interdisciplinary approach between orthodontics and implantology. One of the particularities of this kind of treatment is given by the distal angulation of central incisor’s root, which invades the space required by the dental implant. Any treatment plan should begin with a thorough radiographical analysis of the space and morphological particularities of the central incisors.